Perceptions and experiences of emergency department staff during the implementation of the four-hour rule/national emergency access target policy in Australia: a qualitative social dynamic perspective - Roberto Forero; Shizar Nahidi; Josephine de Costa; Daniel Fatovich; Gerry FitzGerald; Sam Toloo; Sally McCarthy; David Mountain; Nick Gibson; Mohammed Mohsin; Wing Nicola Man (BMC, 2019)
Abstract Background The Four-Hour Rule or National Emergency Access Target policy (4HR/NEAT) was implemented by Australian State and Federal Governments between 2009 and 2014 to address increased demand, overcrowding and access block (boarding) in Emergency Departments (EDs). This qualitative study aimed to assess the impact of 4HR/NEAT on ED staff attitudes and perceptions. This article is part of a series of manuscripts reporting the results of this project. Methods The methodology has been published in this journal. As discussed in the methods paper, we interviewed 119 participants from 16 EDs across New South Wales (NSW), Queensland (QLD), Western Australia (WA) and the Australian Capital Territory (ACT), in 2015-2016. Interviews were recorded, transcribed, imported to NVivo 11 and analysed using content and thematic analysis. Results Three key themes emerged: Stress and morale, Intergroup dynamics, and Interaction with patients. These provided insight into the psycho-social dimensions and organisational structure of EDs at the individual, peer-to-peer, inter-departmental, and staff-patient levels. Conclusion Findings provide information on the social interactions associated with the introduction of the 4HR/NEAT policy and the intended and unintended consequences of its implementation across Australia. These themes allowed us to develop several hypotheses about the driving forces behind the social impact of this policy on ED staff and will allow for development of interventions that are rooted in the rich context of the staff's experiences.